Dynamics of Islamic Religious Education in State Junior High Schools - Rahmawati, Viki; Muhayat, Imam; Triyuliasari, Anisah (Jurnal Pendidikan Nusantara, 2025)
This study was conducted to reveal how the development of a state-based school that still pays attention to Islamic religious education for its students. This study is a field study with data collection techniques through observation through online media, as well as interviews with school officials at SMP Negeri 1 Jetis. While the data analysis technique is an interactive model. The results of the study indicate that in its development SMP Negeri 1 Jetis experienced dynamics in its education system, where these dynamics occurred in various stages including, a) the problem identification stage, namely the principal's anxiety about the importance of Islamic religious education, b) the stage of an alternative problem solver, namely by adding special hours that focus on learning to read and write the Qur'an, c) the stage of choosing a new strategy, namely the full-day school system, d) the implementation stage that takes place and causes changes in an element of education that includes the management of teacher and student recruitment, financing, facilities, infrastructure, and curriculum, and e) the evaluation stage. While the forms of dynamics of SMP Negeri 1 Jetis include two things that include governance and school culture. In terms of governance, it is led by a professional principal whose management is consistently supported by innovative policies. Meanwhile, the school culture is based on a predetermined vision, which then fosters attitudes that are implemented in the daily lives of all members of the school community.